If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -5(x + 3) + x = 6 Reorder the terms: 5 + -5(3 + x) + x = 6 5 + (3 * -5 + x * -5) + x = 6 5 + (-15 + -5x) + x = 6 Combine like terms: 5 + -15 = -10 -10 + -5x + x = 6 Combine like terms: -5x + x = -4x -10 + -4x = 6 Solving -10 + -4x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -4x = 6 + 10 Combine like terms: -10 + 10 = 0 0 + -4x = 6 + 10 -4x = 6 + 10 Combine like terms: 6 + 10 = 16 -4x = 16 Divide each side by '-4'. x = -4 Simplifying x = -4
| 10=r+2 | | 26!/(26-13)!13! | | 7(t+2)=91 | | -19=5-2(a-5)-4(a+1) | | 7t-18=-16+8t | | 85=1+7(n+4) | | 2xy+3y=-72 | | -10[s+5]=-138 | | 12x-8+4x=4x+2+13+10x | | 110=2(6+7x) | | -8(4c-3)=40 | | 2n+3r-6+2n= | | -6-5(-6x+4w)+5w= | | x*x=140000 | | 17u=27+8u | | -2.6y+7.1=43.5 | | u+19=19 | | u-18=15 | | -6.6y+7.4=330.8 | | 4/12-8/6=2/3 | | -6.8y+8.7=132.46 | | r+20=22 | | 11w-5w=24 | | 4y=5t | | 3j=54 | | 91=p+80 | | u+4=19 | | 6-3k=-21 | | -n+5=49.7 | | 12+r=14 | | S+2=2s+1 | | 9k-6=-429.9 |